Real world web services - Iverson, Will (O'Reilly, 2004)
The core idea behind Real World Web Services is simple: after years of hype, what are the major players really doing with web services? Standard bodies may wrangle and platform vendors may preach, but at the end of the day what are the technologies that are actually in use, and how can developers incorporate them into their own applications? Those are the answers Real World Web Services delivers. It's a field guide to the wild and wooly world of non-trivial deployed web services.The heart of the book is a series of projects, demonstrating the use and integration of Google, Amazon, eBay, PayPal, FedEx, and many more web services. Some of these vendors have been extremely successful with their web service deployments: for example, eBay processes over a billion web service requests a month!The author focuses on building 8 fully worked out example web applications that incorporate the best web services available today. The book thoroughly documents how to add functionality like automating listings for auctions, dynamically calculating shipping fees, automatically sending faxes to your suppliers, using an aggregator to pull data from multiple news and web service feeds into a single format or monitoring the latest weblog discussions and Google searches to keep web site visitors on top of topics of interest-by integrating APIs from popular websites most people are already familiar with.For each example application, the author provides a thorough overview, architecture, and full working code examples.This book doesn't engage in an intellectual debate as to the correctness of web services on a theological level. Instead, it focuses on the practical, real world usage of web services as the latest evolution in distributed computing, allowing for structured communication via Internet protocols. As you ll see, this includes everything from sending HTTP GET commands to retrieving an XML document through the use of SOAP and various vendor SDKs.